2017
DOI: 10.3892/ijmm.2017.3007
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic expression, purification and characterization of human cyclooxygenase-2

Abstract: Cyclooxygenase-2 (COX-2) is a key enzyme which catalyzes the conversion of arachidonic acid (AA) into prostaglandins (PGs). It plays an important role in pathophysiological processes, such as tumorigenesis, angiogenesis, inflammation and tumor cell drug resistance. Therefore, COX-2 has been viewed as an important target for cancer therapy. The preparation of COX-2 protein is an important initial step for the subsequent development of COX-2 inhibitors. In this study, we report a strategy to heterologously expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Generally, linoleic acid is reported to prolong and desaturate arachidonic acid, and COX-2 is a key enzyme to catalyze arachidonic acid to produce pro-inammatory factor prostaglandins, which is the rst rate-limiting step in prostaglandin biosynthesis. 39,40 Obviously, the reduction of linoleic acid, 2arachidonylglycerol, prostaglandin E1, and prostaglandin A2 in the TBT group (Fig. 2) suggested that the activation of COX-2 in TBT group was not through the arachidonic acid metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Generally, linoleic acid is reported to prolong and desaturate arachidonic acid, and COX-2 is a key enzyme to catalyze arachidonic acid to produce pro-inammatory factor prostaglandins, which is the rst rate-limiting step in prostaglandin biosynthesis. 39,40 Obviously, the reduction of linoleic acid, 2arachidonylglycerol, prostaglandin E1, and prostaglandin A2 in the TBT group (Fig. 2) suggested that the activation of COX-2 in TBT group was not through the arachidonic acid metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…COX-2, as a key enzyme located on the membrane of ER, was reported to be N-glycosylated in the ER in the absence of arachidonic acid, and then transported to the Golgi apparatus for modication, before nally being transported back to the ER. 39,41 Furthermore, it has been reported to catalyze the biosynthesis of eicosanoid lipids, affecting the expression of eicosanoid-lysolipids in ER. [42][43][44][45] In addition, PERK is an ER transmembrane protein response to ER stress and could promote apoptosis through activating the downstream proapoptotic transcription factor CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control for the IPTG-induced E. coli AK2/HB2151 culture supernatant was supernatant obtained without IPTG induction. Due to the absence of AK2 in PBST containing 3% non-fat milk, PBST with 3% non-fat milk served as the negative control for purified AK2, while wells coated with recombinant human prolyl hydroxylase 2 (rhPHD2) [ 27 ], recombinant human cyclooxygenase-2 (rhCOX-2) [ 46 ] or bovine serum albumin (BSA) served as irrelevant protein controls for rhCDK4.…”
Section: Methodsmentioning
confidence: 99%
“…While full analysis is beyond the scope of this spectroscopic contribution, we hope that this visualization will promote further understanding of the enzymatics involved. The high degree of specificity of lipoxygenase and cyclooxygenase enzymes [18]- [24] should be reevaluated in light of the fact individual sites on the polyunsaturated fatty acid chain are nonequivalent, and each LC-PUFA molecule has an individual, specific structure incorporating torsion.…”
Section: Discussionmentioning
confidence: 99%
“…All five of the PUFA we present are metabolized by cyclooxygenase and lipoxygenase enzymes into an extensive suite of oxylipin metabolites [18]- [24].…”
Section: Introductionmentioning
confidence: 99%